Coating dental implant abutment screws with diamondlike carbon doped with diamond nanoparticles: The effect on maintaining torque after mechanical cycling - Lepesqueur, Laura Soares Souto [UNESP]; de Figueiredo, Viviane Maria Gonçalves [UNESP]; Ferreira, Leandro Lameirão; Sobrinho, Argemiro Soares da Silva; Massi, Marcos; Bottino, Marco Antônio [UNESP]; Nogueira, Lafayette [UNESP] (My University, 2015)
Purpose: To determine the effect of maintaining torque after mechanical cycling of abutment screws that are coated with diamondlike carbon and coated with diamondlike carbon doped with diamond nanoparticles, with external and internal hex connections. Materials and Methods: Sixty implants were divided into six groups according to the type of connection (external or internal hex) and the type of abutment screw (uncoated, coated with diamondlike carbon, and coated with diamondlike carbon doped with diamond nanoparticles). The implants were inserted into polyurethane resin and crowns of nickel chrome were cemented on the implants. The crowns had a hole for access to the screw. The initial torque and the torque after mechanical cycling were measured. The torque values maintained (in percentages) were evaluated. Statistical analysis was performed using one-way analysis of variance and the Tukey test, with a significance level of 5%. Results: The largest torque value was maintained in uncoated screws with external hex connections, a finding that was statistically significant (P = .0001). No statistically significant differences were seen between the groups with and without coating in maintaining torque for screws with internal hex connections (P = .5476). Conclusion: After mechanical cycling, the diamondlike carbon with and without diamond doping on the abutment screws showed no improvement in maintaining torque in external and internal hex connections.
Keywords: Dental implant; Implant screw; Torque